2021
DOI: 10.48550/arxiv.2103.06659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-time diffusion and energy transfer in polydisperse mixtures of particles with different temperatures

Efe Ilker,
Michele Castellana,
Jean-François Joanny

Abstract: Evidence suggests that the transport rate of a passive particle at long timescales is enhanced due to interactions with the surrounding active ones in a size-and composition-dependent manner. The collisions generate additional friction on the particle while, on top of that, for nonequilibrium (active) systems, the collisions can also lead to an exchange of energy between different types of particles. Accordingly, the long-time diffusion coefficient of a tagged particle is shaped by the interplay between the ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Among the different perspectives opened by the present work, it will be particularly interesting to study: (i) such colloids in inhomogeneous environments or under confinement [24], which will affect the polarization of the solute particles around the colloid and its propulsion; (ii) the effect of hydrodynamic interactions, which have been shown to have a dramatic effect on the collective dynamics of active colloids [25][26][27]; (iii) situations where the phase separation is not driven by interparticle interactions but by mixing particles in contact with different thermostats [28][29][30][31].…”
Section: (B)mentioning
confidence: 99%
“…Among the different perspectives opened by the present work, it will be particularly interesting to study: (i) such colloids in inhomogeneous environments or under confinement [24], which will affect the polarization of the solute particles around the colloid and its propulsion; (ii) the effect of hydrodynamic interactions, which have been shown to have a dramatic effect on the collective dynamics of active colloids [25][26][27]; (iii) situations where the phase separation is not driven by interparticle interactions but by mixing particles in contact with different thermostats [28][29][30][31].…”
Section: (B)mentioning
confidence: 99%
“…Discussion and conclusions -Active matter [21] and, in particular, active polymers [12] are an emergent research field in modern soft matter. By employing the twodiffusivities dynamic model introduced and studied in the recent works [13,33,41,45], we have shown that the way nanoprobes diffuse in active-passive polymer mixtures depend on the architecture of the chains. In linear solutions activity disrupts the clustering of nanoprobes seen under purely passive conditions, while in ring solutions the tendency is quite the opposite with nanoprobes separating away from the active polymer component (Fig.…”
mentioning
confidence: 99%